Avaliação econômica e ambiental por meio do mapeamento da logística reversa de resíduos de equipamentos eletroeletrônicos: estudo de múltiplos casos no Brasil - Correia, Auro de Jesus Cardoso (2017)
Due to the excessive consumption and the commercialization of electronic products on a large scale, electronic waste presents itself as a critical and aggressive situation to the environment. This scenario, which indicates the increase in waste generation, has presented itself as a problem for society due to the limited capacity of the landfills and the imminent risk of contamination of the ecosystems by the harmful substances contained in this waste. On the other hand, the disposal of this type of waste can present good economic opportunities due to the presence of metals such as gold, silver, copper, aluminum, palladium, among other possibilities. In view of the foregoing, laws and regulatory instruments create obligatoriness with the purpose of obtaining the implementation of an adequate management for this type of waste. Inserted in this context, this research has the purpose of the economic evaluation in environmental by mapping the reverse logistics of the electrical and electronic waste, seeking to investigate opportunities for economic gains and reduction of final waste disposal in Brazil. In order to reach the objectives of the present study, a study of multiple cases was carried out in three companies of São Paulo, being a North American multinational manufacturer of computers, a company that manages electrical and electronic waste, and finally a manufacturer and importer of electronics, Associated with a representative entity of electronics, founder of a WEEE manager. Information was collected based on responses from semi-structured interviews, direct observations, and documentary data. The results indicated the existence of economic gains and opportunities to increase the financial return to the companies involved in the reverse electric-electronic waste chain in Brazil. In addition, it was possible to verify the reduction of the disposition of the residues coming from the electronic products.